How a mega-grazer copes with the dry season: Food and nutrient intake rates by white rhinoceros in the wild - Shrader, A.M.; Owen-Smith, N.; Ogutu, J. (Wiley, 2006)
Few studies have investigated how free-ranging wild herbivores adjust their food intake rate and nutrient gains during the dry season. Our study focused on the largest extant grazer, the white rhinoceros (Ceratotherium simum Burchell 1817). Field measurements were made on changes in bite mass, bite rate and nutrient concentrations of food eaten during the dry season. 2. As the dry season progressed, the quality and availability of food resources declined. During this time white rhinos foraged mainly in high-quality short and woodland grasslands. Late in the dry season they also used flushes of green grass in previously burnt Themeda grasslands. 3. Bite mass increased linearly with increasing sward height, while bite rate declined. Intake rate was determined primarily by bite mass and thus tended to increase linearly with sward height. Maximum bite mass and intake rate was obtained in swards >20 cm. 4. White rhinos did not compensate for seasonal declines in food quality by adjusting their food intake rate or diet breadth. We suggest that white rhinos mobilize fat reserves to help meet their nutritional needs during the dry season.